Critical information infrastructure protection requirement for the Malaysia public sector - Mohd Sabtu, Saiful Bahari; Mohamad, Kamaruddin Malik
Malaysia Public Sector (MPS) organizations span laterally within all ten critical sectors outlined in the National Cyber Security Policy (NCSP). Critical Information Infrastructure Protection (CIIP) initiatives are driven by the NCSP strategic thrusts and further executed at the sectoral level. However, a dedicated CIIP framework for the MPS is currently lacking thus giving an opportunity for research in this area. This paper explores current CIIP requirements pertinent to MPS sectoral needs using a qualitative approach. The method used is comparative analysis. Resources and reference materials involve international organizations requisites, key national policy documents, published official directives and circulars related to the MPS CIIP. The study findings have shown that risk management and resilience are among the emerging themes. A total of 21 external strategic requirements and 25 available internal resources are identified. A comparison of MPS Cybersecurity Framework (RAKKSSA) against NIST Cybersecurity Framework is also established to highlight CIIP compatibility. For future work, five recommendations are proposed as a guideline for developing MPS CIIP